2013
DOI: 10.3892/mmr.2013.1583
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of TSC1 and TSC2 mutations in American, British, Polish and Taiwanese populations

Abstract: Abstract. Tuberous sclerosis (TS) is caused by mutation of the tumor suppressor genes, tuberous sclerosis complex 1 (TSC1) or 2 (TSC2). The aim of the present study was to compare the frequency and types of TSC1 and TSC2 mutations in American, British, Polish and Taiwanese populations. A meta-analysis of 380 TS patients was performed. Significant differences were analyzed using the Chi-square test and one-way ANOVA analysis. Results showed a difference in frequency for the four populations analyzed. The freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, the difference was not statistically significant (P = 0.051) due to the small sample size. All mutation types, including base substitution, insertions, and deletions, were described in TSC and the distribution of mutation spectrums within both genes is highly heterogeneous [7][8][9]12,15,16,29]. The results in our study demonstrated that nonsense mutations occurred significantly more frequently in TSC1 gene (p = 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…However, the difference was not statistically significant (P = 0.051) due to the small sample size. All mutation types, including base substitution, insertions, and deletions, were described in TSC and the distribution of mutation spectrums within both genes is highly heterogeneous [7][8][9]12,15,16,29]. The results in our study demonstrated that nonsense mutations occurred significantly more frequently in TSC1 gene (p = 0.001).…”
Section: Discussionmentioning
confidence: 50%
“…In turn, these promising findings have inspired the investigation of mTOR inhibitors, such as rapamycin, in patients with TSC. Everolimus, an mTOR inhibitor, is now FDA approved for reduction of Subependymal Giant Cell Astrocytomas (SEGAs) in children with TSC 38 . Now, with safety profiles established, several international studies are investigating the use of mTOR inhibitors for improving the cognitive delays and behavioral deficits found in children with TSC 39 .…”
Section: Targeted Treatment Example 1: Tuberous Sclerosis Complexmentioning
confidence: 99%